Probiotics in Critical Illness: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 8 (25th May 2022) - Sharif, Sameer; Greer, Alisha; Skorupski, Clarissa; Hao, Qiukui; Johnstone, Jennie; Dionne, Joanna C.; Lau, Vincent; Manzanares, William; Eltorki, Mohamed; Duan, Erick; Lauzier, Francois; Marshall, John C.; et al.
Abstract : OBJECTIVES: To determine the safety and efficacy of probiotics or synbiotics on morbidity and mortality in critically ill adults and children. DATA SOURCES: We searched MEDLINE, EMBASE, CENTRAL, and unpublished sources from inception to May 4, 2021. STUDY SELECTION: We performed a systematic search for randomized controlled trials (RCTs) that compared enteral probiotics or synbiotics to placebo or no treatment in critically ill patients. We screened studies independently and in duplicate. DATA EXTRACTION: Independent reviewers extracted data in duplicate. A random-effects model was used to pool data. We assessed the overall certainty of evidence for each outcome using the Grading Recommendations Assessment, Development, and Evaluation approach. DATA SYNTHESIS: Sixty-five RCTs enrolled 8, 483 patients. Probiotics may reduce ventilator-associated pneumonia (VAP) (relative risk [RR], 0.72; 95% CI, 0.59 to 0.89 and risk difference [RD], 6.9% reduction; 95% CI, 2.7–10.2% fewer; low certainty), healthcare-associated pneumonia (HAP) (RR, 0.70; 95% CI, 0.55–0.89; RD, 5.5% reduction; 95% CI, 8.2–2.0% fewer; low certainty), ICU length of stay (LOS) (mean difference [MD], 1.38 days fewer; 95% CI, 0.57–2.19 d fewer; low certainty), hospital LOS (MD, 2.21 d fewer; 95% CI, 1.18–3.24 d fewer; low certainty), and duration of invasive mechanical ventilation (MD, 2.53 d fewer; 95% CI, 1.31–3.74 d fewer; low certainty). Probiotics probably have no effect on mortality (RR, 0.95; 95% CI, 0.87–1.04 and RD, 1.1% reduction; 95% CI, 2.8% reduction to 0.8% increase; moderate certainty). Post hoc sensitivity analyses without high risk of bias studies negated the effect of probiotics on VAP, HAP, and hospital LOS. CONCLUSIONS: Low certainty RCT evidence suggests that probiotics or synbiotics during critical illness may reduce VAP, HAP, ICU and hospital LOS but probably have no effect on mortality.